New features in UML syntax and semantics - Wolski, Michał; Stasiak, Andrzej (Studia Informatica. System and information technology, 2006)
This paper is an overview of the most important new features introduced to version 2.0 of Unified Modeling Language. We denote the changes to existing diagram and present four new modeling techniques. We present the changes in definitions of syntax, semantics and pragmatics of behavioral and static models of systems designed with UML 2.0. Particular emphasis is put on the changes to sequence and activity diagrams and to component diagrams. The newly introduced diagrams, unknown in previous UML versions – interaction overview diagrams, timing diagrams, composite structure diagrams and package diagrams – are described with the most detail.